Kirk-Othmer Encyclopedia of Chemical Technology 2000
DOI: 10.1002/0471238961.1615122504150801.a01
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine‐Containing Polymers, Poly(Vinylidene Fluoride)

Abstract: This article reviews the preparation, properties, and uses of poly(vinylidene fluoride) (PVDF or PVF 2 ), including preparation of 1,1‐difluoroethene or vinylidene fluoride (VDF or ), and commercially important copolymers of VDF with other fluorinated comonomers. PVDF is commercially produced by free‐radical‐initiated polymerization of VDF in emulsion or suspension. It has the characteristic resistance of fluoropolymers to harsh chemical, thermal, ultraviolet, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 75 publications
1
27
0
Order By: Relevance
“…Furthermore, it was shown that the ratio of reverse tail-to-tail addition decreased from 50%, for the first addition of these adducts, to a limit similar to that of PVDF, i.e. 10%, when the chain length increased [1] Generally, the literature reports various defects of chain formation between 6%and 9% for PVDF [2][3][4] or for oligo poly(vinylidenefluoride)(PVDF) [5][6][7] and between 5% and 10% for VDF telomers [8][9][10][11][12]. Recent work has also reported a value of 2.5% from fractionated CF 3-(VDF)-I telomers [13].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was shown that the ratio of reverse tail-to-tail addition decreased from 50%, for the first addition of these adducts, to a limit similar to that of PVDF, i.e. 10%, when the chain length increased [1] Generally, the literature reports various defects of chain formation between 6%and 9% for PVDF [2][3][4] or for oligo poly(vinylidenefluoride)(PVDF) [5][6][7] and between 5% and 10% for VDF telomers [8][9][10][11][12]. Recent work has also reported a value of 2.5% from fractionated CF 3-(VDF)-I telomers [13].…”
Section: Introductionmentioning
confidence: 99%
“…The 15 dry coatings have a thickness of 25.7 AE 4.3 mm. Considering the atomic composition of some of the standard samples and their density (~1.4 g/cm 3 ), we calculated infinite thickness conditions for the XRF analysis by using the software 'XrfTable for Windows'. [11] Results of the calculation indicated that the smallest thickness required to meet infinite thickness conditions was 12 mm for the fluorine Ka line and 5.5 mm for the oxygen Ka line.…”
Section: Development Of Calibration Curves With Clear Coat Standardsmentioning
confidence: 99%
“…Paints using poly (vinylidene fluoride) in particular have a 50-year record history of outstanding performance linked to chemical resistance, durability, adhesion, and low dirt retention, as well as good moisture and fungus resistance. [1][2][3] Classic paint formulation on organic solvent technology, whereas modern paint formulation is based on latex technologies where the polymeric phases and pigments are suspended in an aqueous solvent, thus eliminating the negative environmental impact of the use of organic solvents. Such formulations involve multiple components addressing the need for longevity (weatherability), adhesion, color, and structural integrity.…”
mentioning
confidence: 99%
“…The commercial PVDF polymer is generally produced by polymerization process in emulsion or suspension using free radical initiators and forming a repeating unit of -CH 2 -CF 2 -. The spatial arrangement of the CH 2 and CF 2 groups along the polymer chain have the main effect on the unique properties of PVDF materials in generated from considering the crystalline structure [2]. One of considerable methods to produce PVDF fiber is electrospinning process.…”
Section: Introductionmentioning
confidence: 99%